Analytical Potentiality of Computer - Controlled Background Correction with Electrothermal Atomic Emission Spectrometry : Determination of Copper in Milk Powder (Baghdad Science Journal, 2004)
A fully automatic electrothermal atomic emission spectrometry (ETA-AES) is described. This system is based on an echelle monochromator modified for wave¬length modulation which is completely controlled by microcomputer . The advantages of the system in atomic spectrometry have been discussed . Aspects of the analytical performances such as calibration ? dection limit, precision , and recovery for copper are considered . This system is applied for routine determination of copper in commercial powdered mill? by slurr>' atomization versus aqueous atomization techniques.